Global incidence of serogroup B invasive meningococcal disease: a systematic review. Issue 11 (November 2015) - Sridhar, Shruti; Greenwood, Brian; Head, Christopher; Plotkin, Stanley A; Sáfadi, Marco A; Saha, Samir; Taha, Muhamed-Kheir; Tomori, Oyewale; Gessner, Bradford D
Summary: Use of recently licensed vaccines against Neisseria meningitidis serogroup B (NmB) will depend partly on disease burden estimates. We systematically reviewed NmB incidence and mortality worldwide between January, 2000, and March, 2015, incorporating data from 37 articles and 12 websites. Most countries had a yearly invasive NmB incidence of less than 2 per 100 000 people. Within these relatively low incidence rates (compared with common causes of invasive bacterial diseases), substantial variation was detected between countries, with a notably higher incidence in Australia, Europe, North America, and South America. China and India had reports only of sporadic cases, and except for South Africa, sub-Saharan Africa showed a near absence of disease. In countries with consistently collected data, NmB incidence has tended to decrease, even as the proportion of invasive meningococcal disease cases caused by serogroup B has increased. With few exceptions, case-fatality ratios were fairly consistent, ranging between 3% and 10%. In high-income countries, incidence rates of NmB were relatively low compared with other vaccine-preventable diseases and might be decreasing. High case-fatality ratios, substantial disease-related morbidity, and the threat of outbreaks could nevertheless make NmB an attractive target for preventive and reactive immunisation programmes. The low availability of data from low-income and middle-income countries suggests the need for improved surveillance before vaccination strategies are designed.